2022
DOI: 10.1002/pan3.10408
|View full text |Cite
|
Sign up to set email alerts
|

Integrating biodiversity conservation and local community perspectives in China through human dimensions research

Abstract: 1. Biodiversity in China coexists alongside large ethnically diverse rural human populations within linked 'biocultural' social-ecological systems. Cumulative and changing local anthropogenic pressures linked to human population growth and economic development are driving unsustainable resource exploitation, habitat loss and extensive species declines. However, these pressures vary between species and systems, and efforts to conserve regional biodiversity may also have unintended negative impacts on local comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 111 publications
(156 reference statements)
0
9
0
Order By: Relevance
“…There are many reasons that lead to increased ecological risks in ecologically fragile areas (Larsen et al, 2011; Ma et al, 2022). For the Tibetan Plateau, overgrazing by local herdsmen on the one hand and nature‐based tourism activities carried out by the floating populations on the other hand are becoming the dominant factor increasing the ecological risks on the plateau.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many reasons that lead to increased ecological risks in ecologically fragile areas (Larsen et al, 2011; Ma et al, 2022). For the Tibetan Plateau, overgrazing by local herdsmen on the one hand and nature‐based tourism activities carried out by the floating populations on the other hand are becoming the dominant factor increasing the ecological risks on the plateau.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…There are many reasons that lead to increased ecological risks in ecologically fragile areas (Larsen et al, 2011;Ma et al, 2022). ecology is further extended to the interaction relationship between tourism, the ecological and social system, the path to achieve local sustainable development becomes more complex (Figure 6b).…”
Section: The Ecological and Economic Effects Of Nature-based Tourism ...mentioning
confidence: 99%
“…We also found that primate habitat suitability decreases with increasing GDP (>0; Figure S3), indicating that areas of increased human development and infrastructure are not compatible with primate persistence (Estrada et al., 2022). It is worth noting that most areas of remaining highly suitable habitats for primates are located in economically underdeveloped areas of China (Figure 1c), with 80% of China's impoverished counties located in remote areas, whose natural ecosystem functions quickly degenerate in that of anthropogenic stresses (i.e., ecologically fragile areas) are considered ecologically fragile (Deng et al., 2016; Ma et al., 2022). Our results indicated that the majority of primate species are distributed in impoverished counties, especially in the southwest mountainous of China (Figure 1c).…”
Section: Discussionmentioning
confidence: 99%
“…However, gaps remain in developing robust ways to monitor the extent of trade, especially of lesser-known species ('t Sas-Rolfes et al, 2019). This is a particular concern in regions that have limited capacity in the interdisciplinary research needed to generate evidence on wildlife trade at the local community level (Wang et al, 2021b;Ma et al, 2022). Both legal and illegal wildlife trade is difficult to quantify and is limited by the ability of researchers to gather data systematically, and some conventional market and consumer survey approaches are inadequate because of the clandestine nature of trade activities and networks (Wong, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, gaps remain in developing robust ways to monitor the extent of trade, especially of lesser‐known species (‘t Sas‐Rolfes et al., 2019). This is a particular concern in regions that have limited capacity in the interdisciplinary research needed to generate evidence on wildlife trade at the local community level (Wang et al ., 2021b; Ma et al., 2022).…”
Section: Introductionmentioning
confidence: 99%